2015
DOI: 10.1049/iet-spr.2014.0122
|View full text |Cite
|
Sign up to set email alerts
|

Variable step‐size non‐negative normalised least‐mean‐square‐type algorithm

Abstract: This paper proposes a fast and precise adaptive filtering algorithm for online estimation under a non-negativity constraint. A novel variable step-size (VSS) non-negative normalised least-mean-square (NLMS)-type algorithm based on the mean-square deviation (MSD) analysis with a non-negativity constraint is derived. The NLMS-type algorithm under the non-negativity constraint is derived by using the gradient descent of the given cost function and the fixed-point iteration method. Furthermore, the VSS derived by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Taking partial differentiation of (8) w.r.t. g o and g 1 gives, (10) Rearranging ( 9) and (10) (11) The matrix in (11) is known as Hessian matrix, H. To find the direction vector such that J(w+g) is minimum, (11) From (15) it is observed that SDA requires presence of parameters R and p, but for most of the real time applications these are not known. To address this issue, LMS algorithm is devised.…”
Section: A Newton's Algorithmsmentioning
confidence: 99%
“…Taking partial differentiation of (8) w.r.t. g o and g 1 gives, (10) Rearranging ( 9) and (10) (11) The matrix in (11) is known as Hessian matrix, H. To find the direction vector such that J(w+g) is minimum, (11) From (15) it is observed that SDA requires presence of parameters R and p, but for most of the real time applications these are not known. To address this issue, LMS algorithm is devised.…”
Section: A Newton's Algorithmsmentioning
confidence: 99%
“…Upon applying the algorithm to the linear equalization we can study the various aspects, behaviours, advantages, and drawbacks of the technique. Moreover this technique, which is essentially employed in the field of adaptive filters, has many different applications in the fields of communications, computers and adaptive signal processing in general [26][27][28][29][30] due to its computation simplicity [31]. Figure 1 represents the block diagram of the channel equalization.…”
mentioning
confidence: 99%